1996
DOI: 10.1111/j.1748-5827.1996.tb01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of severity of canine nasal tumours and relationship with survival

Abstract: A radiological assessment of 35 canine nasal tumours using an objective scoring system was carried out and related to patient survival. The scoring system demonstrated significant increases in disease-free interval and survival for dogs with scores of less than 12 compared to those with scores of 12 or above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
(4 reference statements)
5
16
1
Order By: Relevance
“…The most common breed in this study was the Shetland sheepdog; dolichocephalic dogs accounted for 93.8% [2,5,6,11,[13][14][15]. In this study, both the mean and median age of tumor occurrence were 10 years, which was similar to those previously reported [2,3,9,11,[14][15][16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The most common breed in this study was the Shetland sheepdog; dolichocephalic dogs accounted for 93.8% [2,5,6,11,[13][14][15]. In this study, both the mean and median age of tumor occurrence were 10 years, which was similar to those previously reported [2,3,9,11,[14][15][16].…”
Section: Discussionsupporting
confidence: 80%
“…Adenocarcinoma was the most frequent (75.9%), followed by chondrosarcoma (10.7%) and osteosarcoma (4.5%). These patient data were similar to those previously reported [2,3,5,11,13,20].…”
Section: Patientssupporting
confidence: 82%
“…The mean age of the reported cases is similar with previous studies, which have reported a mean age of onset of nine to 10 years [5,8,14]. The prognosis for paranasal tumors without any treatment is poor and euthanasia is chosen in most animals as a result of progressive local invasion of tumor and related problems within three to six months of the onset of clinical signs [18].…”
Section: Discussionsupporting
confidence: 76%
“…Epitelial tumors which are different type of carcinomas constitute 51 to 75% of nasal tumors. The remaining tumors mostly originate from connective tissue, cartilage or bone [5][6][7][8]. Dolichocephalic and mesocephalic breeds are more prone to nasal tumors [1].…”
Section: Introductionmentioning
confidence: 99%
“…The radiographic diagnosis of inflammatory, infectious, and neoplastic lesions within the nasal cavity can be challenging, as radiographic signs are non-specific 16 . Radiographic signs of diseases of the nasal cavity and sinuses demonstrate a spectrum of appearances ranging from minor increases in soft-tissue opacity to lytic bone lesions and expansible masses 8,13,16,17 . Non-destructive patterns are characteristic of acute bacterial and viral infections, early foreign body reactions, nasal haemorrhage, oedema, and LPR, while a destructive pattern is more suggestive of fungal infection or neoplasia.…”
Section: Introductionmentioning
confidence: 99%